2022
DOI: 10.1093/ajcn/nqac024
|View full text |Cite
|
Sign up to set email alerts
|

Effect of severe compared with moderate energy restriction on physical activity among postmenopausal female adults with obesity: a prespecified secondary analysis of the Type of Energy Manipulation for Promoting optimum metabolic health and body composition in Obesity (TEMPO) Diet randomized controlled Trial

Abstract: Background An under-explored strategy for increasing physical activity is the dietary treatment of obesity, but empirical evidence is lacking. Objectives To compare the effects of weight loss via severe versus moderate energy restriction on physical activity over 36 months. Methods 101 postmenopausal female adults (45–65 years, 30–40 kg/m2, <180 minute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Additionally, recent analysis of food diaries of participants of the TEMPO Diet Trial has shown that diet quality improved for all participants from baseline, and this was mostly driven by a reduction in the intake of discretionary foods 46 . The VLED intervention group also showed higher levels of physical activity and lower levels of sedentary behavior at 6 and 12 months, in comparison to the non‐VLED group 47 . Taken together, these factors likely contribute to the longer‐term successful weight loss that is seen in response to VLEDs.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Additionally, recent analysis of food diaries of participants of the TEMPO Diet Trial has shown that diet quality improved for all participants from baseline, and this was mostly driven by a reduction in the intake of discretionary foods 46 . The VLED intervention group also showed higher levels of physical activity and lower levels of sedentary behavior at 6 and 12 months, in comparison to the non‐VLED group 47 . Taken together, these factors likely contribute to the longer‐term successful weight loss that is seen in response to VLEDs.…”
Section: Discussionmentioning
confidence: 96%
“… 46 The VLED intervention group also showed higher levels of physical activity and lower levels of sedentary behavior at 6 and 12 months, in comparison to the non‐VLED group. 47 Taken together, these factors likely contribute to the longer‐term successful weight loss that is seen in response to VLEDs.…”
Section: Discussionmentioning
confidence: 99%